1994
DOI: 10.1038/npp.1994.3
|View full text |Cite
|
Sign up to set email alerts
|

Positron-Emission Tomography and Personality Disorders

Abstract: This study used positron-emission tomography to examine cerebral metabolic rates of glucose (CMRG) in 17 patients with DSM III-R diagnoses of personality disorder. Within the group of 17 personality disorder patients, there was a significant inverse correlation between a life history of aggressive impulse difficulties and regional CMRG in the frontal cortex of the transaxial plane approximately 40 mm above the canthomeatal line (CML) (r = -.56, P = 0.17). Diagnostic groups included antisocial (n = 6), borderli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
105
1
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(112 citation statements)
references
References 18 publications
5
105
1
1
Order By: Relevance
“…We did not find a difference in the orbitofrontal cortical area between depressed patients with BPD and MDD without BPD in contrast to findings from both lesion (Butter et al, 1970;Grafman et al, 1996;Heinrichs, 1989;Raleigh et al, 1979) and neuroimaging studies (De La Fuente et al, 1997;Goyer et al, 1994;New et al, 2002New et al, , 2004Siever et al, 1999) that suggest a role for the orbitofrontal cortex in impulsive aggression. Our sample of depressed women with BPD did not differ significantly in terms of clinical measures of aggression and impulsivity from the depressed women without BPD (see Table 1).…”
Section: Orbitofrontal Cortex In Mdd With Bpd Compared To Mddcontrasting
confidence: 99%
See 2 more Smart Citations
“…We did not find a difference in the orbitofrontal cortical area between depressed patients with BPD and MDD without BPD in contrast to findings from both lesion (Butter et al, 1970;Grafman et al, 1996;Heinrichs, 1989;Raleigh et al, 1979) and neuroimaging studies (De La Fuente et al, 1997;Goyer et al, 1994;New et al, 2002New et al, , 2004Siever et al, 1999) that suggest a role for the orbitofrontal cortex in impulsive aggression. Our sample of depressed women with BPD did not differ significantly in terms of clinical measures of aggression and impulsivity from the depressed women without BPD (see Table 1).…”
Section: Orbitofrontal Cortex In Mdd With Bpd Compared To Mddcontrasting
confidence: 99%
“…Functional neuroimaging studies of brain glucose metabolism in borderline and other aggressive and impulsive patients have also implicated the anterior cingulate area. In agreement with our findings, most studies of BPD found low relative glucose metabolism and regional cerebral blood flow (rCBF) in the anterior cingulate gyrus at rest (De La Fuente et al, 1997;Goyer et al, 1994). PET studies report that FEN responses are blunted in the orbitofrontal cortex and anterior cingulate gyrus (Siever et al, 1999) in impulsive aggressive subjects compared to healthy controls, as are m-CPP responses (New et al, 2002), although not all studies agree (Soloff et al, 2000).…”
Section: Anterior Cingulate In Mdd With Bpd Compared To Mddsupporting
confidence: 87%
See 1 more Smart Citation
“…Neuroimaging studies in subjects with BPD indicate structural and functional changes in brain regions critical to cognitive activity, such as decreases in frontal lobe and hippocampal volumes (Driessen et al, 2000;Lyoo et al, 1998;Rusch et al, 2003), and changes in frontal lobe glucose metabolism (Goyer et al, 1994;De la Fuente et al, 1997;Juengling et al, 2003). Tebartz van Elst et al (2001) report a significant reduction of N-acetylaspartate concentration (a proposed measure of neuronal integrity) in the dorsolateral prefrontal cortex (DLPFC) measured by 1 H-MRS in patients with BPD compared to controls.…”
Section: Da Dysfunction and Impulsive Behaviors In Animalsmentioning
confidence: 99%
“…Positron emission tomography (PET) has revealed reduced prefrontal cortical activity in patients with bipolar depression (Baxter et al 1989), patients with personality disorders characterized by impulsive aggression (Goyer et al 1994), alcoholic criminal offenders with a history of impulsive aggression (Linnoila et al 1983), impulsive murderers (Raine et al 1994), and violent psychiatric inpatients (Volkow and Tancredi 1987). Fenfluramine administration increases cortical metabolism and/or blood flow in orbital frontal cortex in normal subjects (Kapur et al 1994;Mann et al 1996).…”
mentioning
confidence: 99%